Processing and interpretation of gravimetry and magnetometry anomalies in the Azufral Volcano, Nariño, Colombia (2017)
"The purpose of this study is to use geophysical potential methods such as Gravimetry and magnetometry to analyze the data obtained during the survey campaigns in the Altiplano Nariñense in 2008 by the Servicio geológico colombiano, in the zone of influence of the Azufral volcano. the present project was elaborated applying the potential methods and performing multiple operations with the anomaly obtained to contribute in the construction of a better understanding model for the Azufral volcano. The spectral analysis was applied to the magnetic total intensity anomaly to estimate the depth of the Curie isotherm and the thermal gradient, obtaining for the isotherm Curie a depth of 2.24 km and 258.9 C/km thermal gradient for the zone." -- Tomado del Formato de Documento de Grado.